"Superest Ager" - Wolfe, A. B. (Quarterly Journal of Economics, 1925)
“Superest Ager” Get access A. B. Wolfe A. B. Wolfe Ohio State University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 40, Issue 1, November 1925, Pages 172–175, https://doi.org/10.2307/1885821 Published: 01 November 1925